Phytochemicals in the treatment of inflammation-associated diseases: the journey from preclinical trials to clinical practice - Nisar, Akib; Jagtap, Suresh; Vyavahare, Suresh; Deshpande, Manasi; Harsulkar, Abhay; Ranjekar, Prabhakar; Prakash, Om (Frontiers in Pharmacology, 2023)
Advances in biomedical research have demonstrated inflammation and its related diseases, the greatest threat to public health. Inflammatory action is the pathological response of the body toward the external stimuli such as infections, environmental factors, and autoimmune conditions to reduce tissue damage and improve patient comfort. However, when detrimental signal-transduction pathways are activated and inflammatory mediators are released over an extended period of time, the inflammatory process continues and a mild but persistent pro-inflammatory state may develop. Numerous degenerative disorders and chronic health issues including arthritis, diabetes, obesity, cancer, and cardiovascular diseases, among others, are associated with the emergence of a low-grade inflammatory state. Though, anti-inflammatory steroidal, as well as non-steroidal drugs, are extensively used against different inflammatory conditions, they show undesirable side effects upon long-term exposure, at times, leading to life-threatening consequences. Thus, drugs targeting chronic inflammation need to be developed to achieve better therapeutic management without or with a fewer side effect. Plants have been well known for their medicinal use for thousands of years due to their pharmacologically active phytochemicals belonging to diverse chemical classes with a number of these demonstrating potent anti-inflammatory activity. Some typical examples include colchicine (alkaloid), escin (triterpenoid saponin), capsaicin (methoxy phenol), bicyclol (lignan), borneol (monoterpene), and quercetin (flavonoid). These phytochemicals often act via regulating molecular mechanisms that synergize the anti-inflammatory pathways such as increased production of anti-inflammatory cytokines or interfere with the inflammatory pathways such as to reduce the production of pro-inflammatory cytokines and other modulators to improve the underlying pathological condition. This review describes the anti-inflammatory properties of a number of biologically active compounds derived from medicinal plants, and their mechanisms of pharmacological intervention to alleviate inflammation-associated diseases. The emphasis is given to information on anti-inflammatory phytochemicals that have been evaluated at the preclinical and clinical levels. Recent trends and gaps in the development of phytochemical-based anti-inflammatory drugs have also been included.